An evaluation of the effectiveness of safety and health control programmes in the Zimbabwean mining sector: a case study of Mimosa mine - Mundiri, Chida (Midlands State University, 2018)
The study entitled ‘An evaluation of the Safety and Health Control Programmes in the Mining Sector: A case study of Mimosa Mine’, was carried out to find the solutions to the accidents that continue to happen in the mining sector. This was despite the fact that the Mining Sector has invested a lot of resources into Safety and Health and were pursuing a ZERO HARM trajectory which emphasized on Zero Accidents at workplaces. The study employed a descriptive case study approach in its investigation. The Mining Sector, Mining Employees and their Families, the Government and the Researcher were the key beneficiaries of the investigation. The study concluded that the Safety and Healthy Control Programmes were ineffective because of failure by management and employees to play their respective roles in the implementation of safety and health control programmes. Lack of engagement in the Safety and Healthy processes, production pressure and poor attitude of employees towards Safety and Health issues were highlighted as some of the key obstacles to making Safety and Health Control programmes effective. The researcher recommended engagement of employees from the formulation to the evaluation stages of safety and health control programs and attitude training programmes to employees by qualified practitioners among other recommendations preferably those with andragogical experience